Reply to "Comments on 'Optimization of Sparse Frequency Diverse Array With Time-Invariant Spatial-Focusing Beampattern'" - Yang, Yu-Qian; Wang, Hao; Wang, Hai-Qing; Gu, Si-Qi; Xu, Da-Long; Quan, Shuang-Long (IEEE antennas and wireless propagation letters, 2018)
Presents a reply to comments on the paper, “Optimization of sparse frequency diverse array with time-invariant spatialfocusing beampattern,” (Yang, Y.-Q., et al), IEEE Antennas Wireless Propag. Lett., vol. 17, no. 2, pp. 351–354, Feb. 2018.